STUDI NUMERIK PRESSURE DROP PADA SILINDER TANDEM DENGAN PENAMBAHAN SPLITTER PLATE DAN VORTEX GENERATOR DI PENAMPANG SEMPIT - Diastian Vinaya Wijanarko (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2021)
The numerical study of pressure drop on a tandem cylinder with the addition of a splitter plate and a vortex generator with the effect of a blockage ratio has been completed. The cross-sectional height and diameter of the cylinder in this study used H= 125 mm and D= 37.5 mm, respectively. The blockage ratio is 30%. The Reynolds number (Re) is 52100 ≤ Re ≤ 156000. The distance between cylinders is 5 to 8, where “s” is the distance from cylinder one to cylinder two. The dimensions of the splitter plate are L=D, L=1,5D, and L=2D where